Controlled tethering of Ag nanoparticles to alter photocatalytic performance of TiO2. (4th October 2019) - Maity, Jayeta; Das, Subhasis; Bala, Tanushree
Abstract: Here we report a reproducible path for the synthesis of TiO2 -Ag nanocomposites with different percentage of loading of Ag content through three simple steps, where capping ability of oleic acid and chemical reduction by sodium borohydride play the crucial role to fabricate this heterostructure. Surface modification of TiO2 is accomplished with oleic acid to confine Ag nanoparticles site selectively only to the surface of TiO2 . The presence of particular amount of Ag nanoparticles shows an excellent photocatalytic activity in comparison to pristine matrix. It is measured under visible light illumination and TiO2 -Ag nanocomposite is found to degrade methylene blue dye considerably via the mechanism of elongation of lifetime of electron-hole separation in semiconductor TiO2 . All samples were meticulously characterized by FTIR, XRD, XPS, TEM and UV–vis absorption spectral analyses.